SOME FEATURES OF LEARNING TERMINOLOGY IN FOREIGN LANGUAGE LESSONS - Bakirova, Hilola (Журнал иностранных языков и лингвистики, 2021)
The article is devoted to the issues of teaching terminology in order to form lexical competence in foreign language classes. The article discusses the features of teaching terminology and the basics of professional speech, as well as the attendant difficulties and possible ways to eliminate them. It gives attention to the history of the emergence of terms, the sources of their formation, the signs of the term and the translation of special texts as a complex human speech-linguistic activity.